(e^(x)cos(cx))=e^(x)cos(cx)
Differentiate both sides of the equation ((e^(x)cos(cx))=e^(x)cos(cx)).
(d)/(dc) ((e^(x)cos(cx)))=(d)/(dc) (e^(x)cos(cx))
Find the derivative of the expression.
(d)/(dc) (e^(x)cos(cx))
Find the derivative of the expression.
(d)/(dc) e^(x)cos(cx)
The chain rule states that the derivative of a composite function (f o g)' is equal to (f' o g)*g'. To find the derivative of e^(x)cos(cx), find the derivatives of each portion of the function and use the chain rule formula.
(d)/(du) e^(x)cos(u)*(d)/(dc) cx
The derivative of e^(x)cos(u) is -(e^(x)sin(u)).
(d)/(du) e^(x)cos(u)=-(e^(x)sin(u))
Multiply -1 by the e^(x)sin(u) inside the parentheses.
(d)/(du) e^(x)cos(u)=-e^(x)sin(u)
Use the product rule to find the derivative of cx. The product rule states that (fg)'=f'g+fg'.
[(d)/(dc) c](x)+(c)[(d)/(dc) x]
The derivative of c is (dx)/(dc) c=1.
(dx)/(dc) c=1
Substitute the derivative back into the product rule formula.
(d)/(dc) cx=(1)(x)+(c)[(d)/(dc) x]
The derivative of x is (dx)/(dc) x=x'.
(dx)/(dc) x=x'
Substitute the derivative back into the product rule formula.
(d)/(dc) cx=(1)(x)+(c)(x')
Simplify the derivative.
(d)/(dc) cx=x+x'c
Replace the variable u with cx in the expression.
(d)/(du) e^(x)cos(u)=-e^(x)sin((cx))
Replace the variable u with cx in the expression.
x+x'c
Form the derivative by substituting the values for each portion into the chain rule formula.
=-e^(x)sin((cx))*(x+x'c)
Remove the parentheses around the expression -e^(x)xsin((cx))-x'ce^(x)sin((cx)).
(d)/(dc) e^(x)cos(cx)=-e^(x)xsin((cx))-x'ce^(x)sin((cx))
Find the derivative of the expression.
(d)/(dc) e^(x)cos(cx)
The chain rule states that the derivative of a composite function (f o g)' is equal to (f' o g)*g'. To find the derivative of e^(x)cos(cx), find the derivatives of each portion of the function and use the chain rule formula.
(d)/(du) e^(x)cos(u)*(d)/(dc) cx
The derivative of e^(x)cos(u) is -(e^(x)sin(u)).
(d)/(du) e^(x)cos(u)=-(e^(x)sin(u))
Multiply -1 by the e^(x)sin(u) inside the parentheses.
(d)/(du) e^(x)cos(u)=-e^(x)sin(u)
Use the product rule to find the derivative of cx. The product rule states that (fg)'=f'g+fg'.
[(d)/(dc) c](x)+(c)[(d)/(dc) x]
The derivative of c is (dx)/(dc) c=1.
(dx)/(dc) c=1
Substitute the derivative back into the product rule formula.
(d)/(dc) cx=(1)(x)+(c)[(d)/(dc) x]
The derivative of x is (dx)/(dc) x=x'.
(dx)/(dc) x=x'
Substitute the derivative back into the product rule formula.
(d)/(dc) cx=(1)(x)+(c)(x')
Simplify the derivative.
(d)/(dc) cx=x+x'c
Replace the variable u with cx in the expression.
(d)/(du) e^(x)cos(u)=-e^(x)sin((cx))
Replace the variable u with cx in the expression.
x+x'c
Form the derivative by substituting the values for each portion into the chain rule formula.
=-e^(x)sin((cx))*(x+x'c)
Remove the parentheses around the expression -e^(x)xsin((cx))-x'ce^(x)sin((cx)).
(d)/(dc) e^(x)cos(cx)=-e^(x)xsin((cx))-x'ce^(x)sin((cx))
Form the equation involving x'
-e^(x)xsin((cx))-x'ce^(x)sin((cx))=-e^(x)xsin((cx))-x'ce^(x)sin((cx))
Remove the parentheses around the expression cx.
-e^(x)xsin((cx))-x'ce^(x)sin((cx))=-e^(x)x(sin(cx))-x'ce^(x)sin((cx))
Remove the extra parentheses around the factors.
-e^(x)xsin((cx))-x'ce^(x)sin((cx))=-e^(x)xsin(cx)-x'ce^(x)sin((cx))
Remove the parentheses around the expression cx.
-e^(x)xsin((cx))-x'ce^(x)sin((cx))=-e^(x)xsin(cx)-x'ce^(x)(sin(cx))
Remove the extra parentheses around the factors.
-e^(x)xsin((cx))-x'ce^(x)sin((cx))=-e^(x)xsin(cx)-x'ce^(x)sin(cx)
Remove the parentheses around the expression cx.
-e^(x)x(sin(cx))-x'ce^(x)sin((cx))=-e^(x)xsin(cx)-x'ce^(x)sin(cx)
Remove the extra parentheses around the factors.
-e^(x)xsin(cx)-x'ce^(x)sin((cx))=-e^(x)xsin(cx)-x'ce^(x)sin(cx)
Remove the parentheses around the expression cx.
-e^(x)xsin(cx)-x'ce^(x)(sin(cx))=-e^(x)xsin(cx)-x'ce^(x)sin(cx)
Remove the extra parentheses around the factors.
-e^(x)xsin(cx)-x'ce^(x)sin(cx)=-e^(x)xsin(cx)-x'ce^(x)sin(cx)
Since -x'ce^(x)sin(cx) contains the variable to solve for, move it to the left-hand side of the equation by adding x'ce^(x)sin(cx) to both sides.
-e^(x)xsin(cx)-x'ce^(x)sin(cx)+x'ce^(x)sin(cx)=-e^(x)xsin(cx)
Since -x'ce^(x)sin(cx) and x'ce^(x)sin(cx) are like terms, subtract x'ce^(x)sin(cx) from -x'ce^(x)sin(cx) to get 0.
-e^(x)xsin(cx)=-e^(x)xsin(cx)
Since the bases are the same, then two expressions are only equal if the exponents are also equal.
x=x
Since x contains the variable to solve for, move it to the left-hand side of the equation by subtracting x from both sides.
x-x=0
Since x and -x are like terms, add -x to x to get 0.
0=0
Since 0=0, the equation will always be true.
(dx)/(dc)=Alwx'ys True